Experimental study on the factor affecting coagulation and flocculation - Helmi, Mohamad Jamil. (UNIMAS, 2005)
The report is concentrate on the investigation of factor affecting coagulation and flocculation. The analysis is profoundly focusing on the raw water at Batang Samarahan, Sg. Sarawak and Sg. Sarawak Kiri. The effective and efficiency of coagulation and flocculation is interrelated on many factors. Previous studies indicated that the pH, alkalinity, turbidity, types and amount of coagulant and coagulant aids, temperature, detention time for flocs formation and the rate of speeding mixture are affecting the huge consequence of coagulation and flocculation process. The thesis is concentrate on the optimum amount of Al(SO 4)3as a coagulant, Ca(OH)2as a coagulant aids and polyelectrolyte as a flocculent to achieve significant treatment, influence of pH, and detention time for flocs agglomeration. The adequate examination and results are required to enable the raw water from all these rivers are treated with save haven for end user around the Kuching region. The problem is solved by first and foremost conducting the laboratory jar test. There are also included several experiment procedure, for instance pH determination and turbidity to achieve the efficient results. The experiment is implemented at Water Treatment Plant, Kuching Water Board, Batu Kitang, Bau, Sarawak. The investigation are found that the quality of raw water at Batang Samarahan required Al(SO4)3in the range of 95 ppm, Ca(OH)2in the range of 2.0 ppm and polyelectrolyte in the range of 0.1 ppm. The Sg. Sarawak required 20 ppm of Al(SO4)3, 1.0 ppm of Ca(OH)2and 0.05 ppm of polyelectrolyte. For Sarawak Kiri 25 ppm of Al(SO4)3, 1.2 ppm of Ca(OH)2e and 0.2 ppm of polyelectrolyte required. The alkalinity of the raw water is a dominant factor that causing the differences in applyingthe amount of coagulant and coagulant aid. The pH value for optimum coagulation and flocculation is achieved around 7. The experiment also found that larger flocs formation needed the smaller time for settling because the colloidal concentration is highest.